2020
DOI: 10.1177/0144598720912344
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and hydrocarbon significance of the coaly source rocks from the Pinghu Formation in the Xihu Sag, East China Sea Shelf Basin

Abstract: The Xihu Sag in the East China Sea Shelf Basin contains abundant oil and gas reserves and is a focus for hydrocarbon exploration and development. Source rocks are mainly coals and coal-measures mudstones in the Paleogene Pinghu and Huagang formations. Samples from the Pinghu Formation in the Xihu Sag were collected for petrology, total organic carbon, and Rock-Eval analysis for the purpose of investigating macerals component and their contributions to hydrocarbon generation potential. The coaly source rocks fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“… 13 Liu suggested that effective HI values of the Pinghu coal were elevated about 0–99 mg·HC/g·TOC with an average of 33 mg·HC/g·TOC compared to the measured HI values. 27 As a result, the organic abundance in our analyzed samples could be an underestimate, and oil-prone source rocks should have occupied a larger proportion. Hydrocarbon expulsion will occur when EOM yields are >30 mg·HC/g·TOC.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“… 13 Liu suggested that effective HI values of the Pinghu coal were elevated about 0–99 mg·HC/g·TOC with an average of 33 mg·HC/g·TOC compared to the measured HI values. 27 As a result, the organic abundance in our analyzed samples could be an underestimate, and oil-prone source rocks should have occupied a larger proportion. Hydrocarbon expulsion will occur when EOM yields are >30 mg·HC/g·TOC.…”
Section: Discussionmentioning
confidence: 88%
“…A predominance of type II kerogen of the coaly source rocks in the Pinghu Formation has been reported by Liu et al based on petrology methods. 27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the Pinghu coal deposits contain significantly higher amount of liptinite (1.47-23.02%; Kang et al, 2020) than the Laisong coals. The vitrinite reflectance of the Pinghu coals (0.55-1.28%) is also much higher than the Laisong coal, owing to deeper depth of burial and steeper geothermal gradient in the Xihu Sag (Liu et al, 2020) (Kang et al, 2020). The coal measure of the Oligocene Yacheng Formation is the most important source rock sequence in the Qiongdongnan Basin in the South China Sea region that had entered a phase of mass gas generation, owing to its high degree of thermal evolution and subsidence (Gongcheng et al, 2019).…”
Section: Comparisons With Regional Depositsmentioning
confidence: 99%